THE INFLUENCE OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION OF WORKMOTIVATION AND ITS IMPACT ON THE PERFORMANCE OF EMPLOYEES OF PT. PLN (PERSERO) REGION OF ACEH - Oriza Sativa; Mukhlis Yunus; M. Shabri Abd Majid (Jurnal Manajemen Inovasi, 2018)
The purpose of this research is to know the partial or simultaneous nfluence of organizational culture and job satisfaction on the motivation of working employees of PT. PLN (Persero) in the region of Aceh, to know the influence of organizational culture and job satisfaction either partially or simultaneous to the performance of theemployees of PT. PLN (Persero) region of Aceh, to knowthe influence of motivational work both partially or simultaneous to the performance of the employees of PT. PLN (Persero) region of Aceh, to find out the influence of organizational culture and job satisfaction either partially or simultaneous performance of  employees through employee motivation PT. PLN (Persero) region of Aceh. Study sample as many as 106 employees of PT. PLN (Persero) region of Aceh is taken by simple random sampling technique. Data analysis tools are used path analysis. The results of the research showed: first hypothesis showed that organizational culture and job satisfaction simultaneously affected the working motivation variables. The second hypothesis can explain that the variables of organizational culture and job satisfaction are interlinkedin order to enhance the performance of employees.The thirdhypothesisshows a positive effect of work motivation on performance. The fourth hypothesis, there is no direct influence on the organizational culture and job satisfaction of employees through the motivation of working performance. Submission of the results of direct and indirect influence can be concluded that the results of the research hypothesis rejects the null hypothesis and accept the alternative. Keywords Organizational Culture, Job Satisfaction, Work Motivation, Employee Performance